The party killer : a Julian Quist mystery novel - Pentecost, Hugh. (New York : Dodd, Mead & Company, 1985)
When an explosion at comedian Larry Lewis's new resort kills two people, Julian Quist discovers secrets that could either prevent another tragedy--or get him killed.
Keywords: MYSTERY -- NOVEL